Emergency department admission and hospitalization for COPD exacerbation and particulate matter short-term exposure in Brescia, a highly polluted town in northern Italy. (April 2021) - Pini, Laura; Giordani, Jordan; Gardini, Giulia; Concoreggi, Carlo; Pini, Alessandro; Perger, Elisa; Vizzardi, Enrico; Di Bona, Danilo; Cappelli, Carlo; Ciarfaglia, Manuela; Tantucci, Claudio
Abstract: Background: Short-term exposure to high Particulate Matter (PM) concentrations worsens several respiratory conditions. Objectives: We evaluated the relationship between short-term exposure to Particulate Matter and fine Particulate Matter (PM10 – PM2.5) and Emergency Department (ED) admissions and hospitalizations for COPD exacerbation observed at the University Hospital, Spedali Civili of Brescia, a city with some of the highest yearly levels of air pollution in Italy. Methods: We collected data from patients admitted to the ED with a COPD exacerbation diagnosis, starting from January 2014 to January 2016. Daily PM levels were collected from the Environmental Protection Regional Agency (ARPA). We performed a time-series analysis using the Poisson regression model with single and multiple day-lag. Results were expressed as Relative Risk (RR) and Excess of Relative Risk (ER) for COPD exacerbation-related ED admissions and hospitalizations, over a 10μg/m3 increase in PM concentration. Results: We collected data from 431 COPD patients. Both PM10 and PM2.5 were significantly associated with the risk of COPD exacerbation-related ED admission and hospitalization. Each increase of 10μg/m3 of PM10 and PM2.5 corresponded respectively to a RR for ED admissions of 1.06 and 1.08 at lag0-1; 1.06 and 1.09 at lag0-5 (p < 0.05). Similar results for COPD Exacerbation-related hospitalizations were found, with a RR of 1.07 and 1.10 at lag0-1 and 1.07 and 1.11 at lag0-5 for each increase of 10μg/m3 PM10 and PM2.5, respectively. Conclusions: Our findings show that in a highly polluted city of Northern Italy, short-term increase in exposure to PM10-PM2.5 is associated with a higher risk of ED admission and hospitalization due to COPD exacerbation with a greater incidence during the winter season. Highlights: Short-term exposure to Particulate Matter worsens several respiratory conditions. Exposure to PM10-PM2.5 relates with higher ED admissions for COPD exacerbation. Exposure to PM10-PM2.5 relates with higher hospitalizations for COPD exacerbation. The incidence of admission and hospitalization is greater during the winter season.